2003
DOI: 10.1128/jb.185.1.302-310.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Previously Unrecognized Step in Pentachlorophenol Degradation in Sphingobium chlorophenolicum Is Catalyzed by Tetrachlorobenzoquinone Reductase (PcpD)

Abstract: The first step in the pentachlorophenol (PCP) degradation pathway in Sphingobium chlorophenolicum has been believed for more than a decade to be conversion of PCP to tetrachlorohydroquinone. We show here that PCP is actually converted to tetrachlorobenzoquinone, which is subsequently reduced to tetrachlorohydroquinone by PcpD, a protein that had previously been suggested to be a PCP hydroxylase reductase. pcpD is immediately downstream of pcpB, the gene encoding PCP hydroxylase (PCP monooxygenase). Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
93
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 29 publications
2
93
1
1
Order By: Relevance
“…Methyl-5-nitrocatechol 5-monooxygenase of Burkholderia strain DNT4 converts 4-methyl-5-nitrocatechol to relatively stable 2-hydroxy-5-methylquinone with nitrite elimination, and the bacterium has a quinone reductase to reduce the quinone to 2-hydroxy-5-methylquinol (22). Sphingomobium chlorophenolicum pentachlorophenol 4-monooxygenase converts pentachlorophenol to tetrachloroquinol with the consumption of 1 O 2 and 2 NADH (32); however, the enzyme really produces tetrachloroquinone, which is not stable and is immediately reduced to tetrachloroquinol by chemical reaction or enzymatic reactions at the expense of NADH (21). A direct comparison of normal oxidation and dechlorinating oxidation by TftD of B. cepacia AC1100 is shown in Fig.…”
Section: Fig 4 the Mass Spectra Of Acetylated 6-chlorohydroxyquinolmentioning
confidence: 99%
See 2 more Smart Citations
“…Methyl-5-nitrocatechol 5-monooxygenase of Burkholderia strain DNT4 converts 4-methyl-5-nitrocatechol to relatively stable 2-hydroxy-5-methylquinone with nitrite elimination, and the bacterium has a quinone reductase to reduce the quinone to 2-hydroxy-5-methylquinol (22). Sphingomobium chlorophenolicum pentachlorophenol 4-monooxygenase converts pentachlorophenol to tetrachloroquinol with the consumption of 1 O 2 and 2 NADH (32); however, the enzyme really produces tetrachloroquinone, which is not stable and is immediately reduced to tetrachloroquinol by chemical reaction or enzymatic reactions at the expense of NADH (21). A direct comparison of normal oxidation and dechlorinating oxidation by TftD of B. cepacia AC1100 is shown in Fig.…”
Section: Fig 4 the Mass Spectra Of Acetylated 6-chlorohydroxyquinolmentioning
confidence: 99%
“…NADH, ascorbate; Refs. 20,21) or by quinone reductases (20,21). It is likely the produced 2,6-dichloroquinone has two fates: the minor one is to be reduced to 2,6-dichloroquinol by reducing agents in the reaction mixture, and the major one is to be hydrolyzed by TcpA to 6-chlorohydroxyquinone, which is chemically reduced to 6-chlorohydroxyquinol.…”
Section: Fig 4 the Mass Spectra Of Acetylated 6-chlorohydroxyquinolmentioning
confidence: 99%
See 1 more Smart Citation
“…Like these microbes, S. chlorophenolicum contains a gene encoding a reductase (PcpD) immediately downstream of the gene encoding the hydroxylase (PcpB). We have previously shown that pcpD is essential for survival of S. chlorophenolicum at high concentrations of PCP but is not essential for survival at high concentrations of 2,3,5,6-tetrachlorophenol (TCP) (2). In this work, we have addressed the mechanism of that protection.…”
mentioning
confidence: 99%
“…2B). In addition, we have previously reported that incubation of PcpB with TCBQ causes loss of catalytic activity (2).…”
mentioning
confidence: 99%